Neurogenic bladder in a young female - Devaraj, Navin Kumar; Abdul Rashid, Aneesa (2018)
This is an uncommon case of 25 year old female, who presented with lower abdominal pain and lower urinary tract symptoms along with suprapubic distension. Initially was thought to be a pelvic malignancy, but through ultrasound examination was found to be due to neurogenic bladder.